D-dimer level is a useful predictor for mortality in patients with COVID-19: Analysis of 483 cases. Issue 6 (November 2020) - Soni, Mamta; Gopalakrishnan, Ram; Vaishya, Raju; Prabu, P.
Abstract: Background and aims: COVID-19 is a multi-system disease, with coagulation abnormalities. D-dimer levels are increased in this disease. We aimed to determine the association of D-dimer levels and mortality and to establish its optimal cut off values in predicting mortality. Association of D-dimer levels with diabetes mellitus has also been established. Methods: Information on 483 patients with confirmed COVID-19 was retrospectively collected and analyzed. The optimal D-dimer cutoff point and C-statistic of routine tests both on admission and during hospital stay were evaluated by receiver operator characteristic (ROC) curve. Results: D-dimer elevation (≥0.50 μg/mL) was seen in 80.1% of the hospitalized patients. D-dimer level ≥2.01 μg/mL was a significant predictor of subsequent deaths ( P < 0.01; HR, 3.165; 95% CI, 2.013–4.977). High D-dimer values (≥0.50 μg/mL) were observed in 72 of the 75 (96%) cases with a fatal outcome. Median D-dimer value among non-survivors was 6.34 μg/mL and among survivors it was 0.94 μg/mL. A higher proportion of fatal outcomes occurred in patients with underlying disease (89.0%), most prominent of which was diabetes mellitus (66%). The median D-dimer value was found to be significantly high in diabetic patients (1.68 μg/mL). Conclusions: Among the measured coagulation parameters, D-dimer during hospital stay had the highest C-index to predict in-hospital mortality in COVID-19 patients. D-dimer value ≥ 2.01 μg/mL can effectively predict in-hospital mortality in patients with COVID-19. A significant association of increased D-dimer level has been found with diabetes mellitus and elderly age. Highlights: D-dimer ≥2.01 μg/ml FEU (fourfold increase) during hospital stay might be the optimum cutoff to predict mortality. Elderly age and diabetes were significantly associated with elevated D-dimer levels, disease severity and mortality. Median D-dimer values were calculated for age, gender, survivors/non-survivors, and diabetic/non - diabetics.